Answer:
D
Step-by-step explanation:
I think it is D
Ok so this question:
y + 1 = - ( x - 2 ) (distribute the negative inside the parenthesis)
y + 1 = -x + 2 (substitute the y= -1)
-1 + 1 = -x + 2
0 = -x + 2 (take two to the other side)
-2 = -x (divide the negative away from x)
2 = x
Answer:
Step-by-step explanation:
Answer:
x=3 and x=-1.25
Step-by-step explanation:
4x^2-7x=15
subtract 15 from each side:
4x^2-7x-15=0
factor (trying different numbers that the sum is 7 and the quotient is 15)
(2x-6 )(2x+2.5 )=0
2x-6=0 add 6 to each side
2x=6
x=3
2x+2.5=0 subtract 2.5 from each side
2x=-2.5
x=-1.25